PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PT. POS INDONESIA CABANG PAMULANG TANGERANG SELATAN - Nurhalizah, Shinta; Sari Octaviani, Irma (Journal of Research and Publication Innovation, 2024)
The purpose of this research is to determine the influence of work motivation and work discipline on employee performance at PT. POS INDONESIA PAMULANG SOUTH TANGERANG BRANCH. The method used is quantitative. The sampling technique used saturated sampling and a sample of 80 respondents was obtained. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, coefficients of determination and hypothesis testing. The results of this research are that work motivation has a significant effect on employee performance with a coefficient of determination value of 54.8% and the hypothesis test obtained t_count > t_tabel or (9.723 > 1.991). Work Discipline has a significant effect on employee performance with a coefficient of determination value of 68.2% and the hypothesis test obtained t_count > t_table or (12.935 > 1.991). Work Motivation and Work Discipline simultaneously have a significant effect on employee performance with the regression equation Y = 5.201 + 0.251X_1 + 0.612X_2. The coefficient of determination value is 70.5% while the remaining 29.5% is influenced by other factors. Hypothesis testing obtained a value of F_count > F_table or (91.897 > 2.720).